Self-tracking while doing sport: Comfort, motivation, attention and lifestyle of athletes using personal informatics tools - Rapp, A.; Tirabeni, L. (International Journal of Human-Computer Studies, 2020)
The spread of wearable technologies is paving the way for the mass-scale adoption of self-tracking instruments, which are progressively integrating into different social practices. Among these, sport seems to be a promising domain in which Personal Informatics tools can support individuals in performing their activities and in achieving their situated goals. In this article, we conducted semi-structured interviews with amateur and elite athletes to explore what they seek in their trackers, how such instruments may impact on their "mind", by affecting their motivation and attention during workouts and races, and how sports data are intertwined with other information pertaining to their lifestyle. On the basis of these findings we discussed three themes that may be relevant for Personal Informatics, also proposing a series of implications for design that may help researchers in designing self-tracking tools for sport.